The role of quantitative safety evaluation in regulatory decision making of drugs. Issue 1 (2nd January 2016) - Chakravarty, Aloka G.; Izem, Rima; Keeton, Stephine; Kim, Clara Y.; Levenson, Mark S.; Soukup, Mat
ABSTRACT: Evaluation of safety is a critical component of drug review at the US Food and Drug Administration (FDA). Statisticians are playing an increasingly visible role in quantitative safety evaluation and regulatory decision-making. This article reviews the history and the recent events relating to quantitative drug safety evaluation at the FDA. The article then focuses on five active areas of quantitative drug safety evaluation and the role Division of Biometrics VII (DBVII) plays in these areas, namely meta-analysis for safety evaluation, large safety outcome trials, post-marketing requirements (PMRs), the Sentinel Initiative, and the evaluation of risk from extended/long-acting opioids. This article will focus chiefly on developments related to quantitative drug safety evaluation and not on the many additional developments in drug safety in general.